SEJARAH DAN PERKEMBANGAN AMALAN PEMBAHAGIAN HARTA SEPENCARIAN DALAM MASYARAKAT ISLAM DI MALAYSIA (History and Development of Harta Sepencarian Distribution Practice in Muslims Society in Malaysia) - Mat Hussin, Mohd. Norhusairi; Daud, Mohd Zaidi (Journal of Al-Tamaddun, 2020)
Harta Sepencarian (jointly acquired property) has been practiced for decades by the Malay society. In fact, this practice is in line with the existence of Malay custom especially Adat Perpatih and Adat Temenggung. Customs is something that can never be separated from historical studies, particularly when it involves the origin of matters in a society. Hence, this article explored the practice of the harta sepencarian (jointly acquired property) and its development according to the history of Malay custom. This article used library research as a method of data collection and was then analyzed through thematic content analysis. All this method applied in researching aspects of harta sepencarian (jointly acquired property) practice in the society. In addition to other academic writing, some examples of cases that had been decided by the Court also has been elaborated to show evidence that the practice of harta sepencarian (jointly acquired property) has been accepted and practiced by the community over the years. Therefore, this study found that the practice of Harta Sepencarian (jointly acquired property) is not something new, but it has been part of the Malay customs history not only in Malaysia but also in Malay Archipelago, mainly in Southeast Asia. Besides that, Harta Sepencarian (jointly acquired property) which was associated with Malay custom and is now recognized by Islamic law and Malaysia’s jurisprudence surely has its own uniqueness and identity.